2007
DOI: 10.1091/mbc.e06-09-0805
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Ciliogenesis inCaenorhabditis elegans: Assignment of IFT Components into Distinct Modules Based on Transport and Phenotypic Profiles

Abstract: Sensory cilium biogenesis within Caenorhabditis elegans neurons depends on the kinesin-2-dependent intraflagellar transport (IFT) of ciliary precursors associated with IFT particles to the axoneme tip. Here we analyzed the molecular organization of the IFT machinery by comparing the in vivo transport and phenotypic profiles of multiple proteins involved in IFT and ciliogenesis. Based on their motility in wild-type and bbs (Bardet-Biedl syndrome) mutants, IFT proteins were classified into groups with similar tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
173
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(181 citation statements)
references
References 71 publications
7
173
1
Order By: Relevance
“…The domain organizations of HICp40 were re-drawn ( Figure 1C). Ou et al identified a novel ciliary protein of F35D11.11B in Caenorhabditis elegans [8]. We re-illustrated the functional domain structures of F35D11.11B ( Figure 1D).…”
mentioning
confidence: 70%
“…The domain organizations of HICp40 were re-drawn ( Figure 1C). Ou et al identified a novel ciliary protein of F35D11.11B in Caenorhabditis elegans [8]. We re-illustrated the functional domain structures of F35D11.11B ( Figure 1D).…”
mentioning
confidence: 70%
“…Nature of allele a References bbs-8(nx77) deletion (Blacque et al 2004 deletion (Ou et al 2007 deletion deletion deletion Li et al 2010) arl-13(gk513) deletion missense (Dwyer et al 1998) unc-101(m1) nonsense (Dwyer et al 2001) daf-25(m98) deletion (Jensen et al 2010) daf-25(m362) deletion deletion deletion deletion (Williams et al 2011) nphp-4(tm925) deletion …”
Section: Gene (Allele)mentioning
confidence: 99%
“…This complex functions in biogenesis of the ciliary membrane (9), trafficking some proteins to or within the ciliary compartment (10), and/or coordinating IFT particle assembly or movement (7,8). Recently, BBSome complexes were shown to form a coat on membranes in vitro (11); this polymerization might underlie some of the functions of the complex.…”
mentioning
confidence: 99%
“…BBS proteins are not thought to be essential structural proteins as the basal body and cilium remain largely intact in most mutant BBS models (3)(4)(5). Disruption of individual BBS genes leads to defects in intraflagellar transport (IFT), a process essential for protein trafficking within the cilium (6)(7)(8).…”
mentioning
confidence: 99%